Intensive Care Unit Infections and Antibiotic Use - Ayşegül Yeşilkaya; Hande Arslan (Galenos Yayinevi, 2011)
Burn wound infections is the leading cause of morbidity and mortality in burn trauma patients. Although burn wound is sterile at the beginning, because of risk factors such as prolonged hospital stay, immunesuppression and burn affecting large body surface area, colonisation firstly with Staphylococcus aureus and then Pseudomonas aeruginosa will occur later. Delay in wound closure and treatment with broad-spectrum antibiotic will result wound colonisation with antibiotic-resistant bacteria. To control colonization and to prevent burn wound infection topical antimicrobial dressings are used. The criteria used for the diagnosis of sepsis and wound infections are different in burn victims. Surface swabs from burn wounds must be cultured for the early assestment of infection. Although histopathological examination and quantitative culture of wound tissue biopsy has been known as the gold standard for the verification of invasive burn wound infection, many burn centers cannot do histopathological examination. When the traditional treatment modalities such as debridement of necrotic tissue, cleaning of wound and topical antimicrobial dressing application fails in the management of burn patient, cultures must be taken from possible foci of infection for the early diagnosis. After specimen collection, empirical bactericidal systemic antibiotic treatment should be started promptly. Inappropriate utilization of antibiotics may cause selection of resistant bacteria in the flora of the patient and of the burn unit which facilitates an infection or an outbreak at the end. Infection control in the burn unit includes surveillance cultures, cohort patient care staff, standard isolation precautions, strict hand hygiene compliance and appropariate antibiotic utilization. (Journal of the Turkish Society Intensive Care 2011; 9 Suppl: 55-61)